The effects of endosulfan on the expression levels of DNA damage and apoptotic genes in HT22 cells: First preliminary study (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the IC50 dose of endosulfan in the hippocampal HT22 cell line, and also to elucidate the effect of expression of DNA-PK, Bax, Bcl2 and Casp-3 genes involved in DNA repair and apoptotic pathway.Material and Methods: Cytotoxic effect of endosulfan and IC50 dose were determined by using XTT method after 24 hours of culture by applying endosulfan at 5 different concentrations (10, 25, 50, 75 and 100 μM) to HT22 cell lines.HT22 cells were then seeded into 6 sterile plates and treated with Endosulfan at IC50 for 12 hours. The expression changes of DNA-Pk, Bax, Bcl2 and Casp-3 genes, after total RNA isolation and cDNA formation, were determined by RT-PCR. Expression levels were calculated using the comparative 2-ΔΔCt method.Results: After 24 hours of endosulfan treatment at different doses in HT22 cell lines, a significant loss of viability was observed in all endosulfan treated groups. It was determined by XTT test, that the IC50 dose of endosulfan was 50 μM in 24 hours treatment. After 12 hours administration of IC50 endosulfan dose in HT22 cells following the examinations of DNA-PK and some apoptotic genes we observed different amounts of increases in expression as follows; 5-fold for DNA-PK, 18-fold for Bax, and 4-fold for Casp-3. On the other hand, approximately 2-fold decrease was detected in Bcl-2 gene.Conclusion: The IC50 dose of 24-hour endosulfan administration in HT22 cell lines was found to be 50 μM. Expression changes in the proapoptotic and antiapoptotic genes have shown that apoptosis is induced in endosulfan-administrated cells. In addition, the increase in DNA-PK gene expression suggests that endosulfan causes DNA damage in cells and triggers DNA repair mechanisms
Keywords: Apoptosis; DNA-PK; endosulfan; HT22